The impact of digital technologies on SME business performance in South Africa - Mdhluli, Mfanasibili Emmanuel (University of the Witwatersrand, Johannesburg, 2024)
In the era of digital transformation and digital technologies, small and medium enterprises (SMEs) face an ever-changing operating environment where being digitally savvy is critical for success. Therefore, adopting and using digital technology may prove to be an important decision that may lead to SMEs continuing to operate as going concerns, growing and being sustainable well into the future. This research delves into the impact of SMEs using digital technologies on business performance. While a myriad of business performance metrics can be tested, for this research, revenue, profit, operational efficiency, customer satisfaction, innovation, risk management and the economic indicator of job creation are analysed. The challenges faced by SMEs are well documented, but there seems to be a lack of research on the benefits and impact of using digital technologies. Faced with limited resources, SMEs must make strategic decisions to drive their businesses forward and investing in digital technologies is one of them. This study seeks to understand the rationale of deciding to use digital technologies utilising the extended technology adoption model (TAM2) coupled with business measures. A quantitative electronic survey was used to collect the data from a sample of 84 South African SMEs. The findings reveal that using digital technologies has a positive impact on SME business performance, thus making it imperative for SMEs to adopt and use digital technologies as part of their business models. The findings elucidate that using digital technologies is not merely an operational imperative, but is also transformative, unlocking sustained competitiveness. The study adds to the literature on the understanding of the impact of using digital technologies on SME business performance, especially from a South African context
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Business performance; SME; Digital technologies; UCTD; SDG-9: Industry, innovation and infrastructure